2020
DOI: 10.17049/ataunihem.701617
|View full text |Cite
|
Sign up to set email alerts
|

Cerrahi̇ Kli̇ni̇klerde Çalişan Hemşi̇releri̇n Hasta Güvenli̇ği̇ Kültürleri̇ Ve Etki̇leyen Faktörler

Abstract: Ölçekten alınan toplam puan ortalamasının 2.81±0.46 olduğu saptanmıştır. Alınan en yüksek puan "çalışan eğitimi" ve "çalışan davranışı" alt boyutlarına, en düşük puan ise "yönetim liderlik" alt boyutuna aittir. Hemşirelerin mesleki memnuniyet ve haftalık mesai saatlerine göre hasta güvenliği kültürleri arasında anlamlı fark tespit edilmiştir. Sonuç: Elde edilen bulgular, katılımcı hemşirelerde hasta güvenliği kültürünün orta düzeyde olduğu şeklinde yorumlanabilir. Hasta güvenliğini sağlamak için sağlık hizmeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…In a study conducted at Başkent University Ankara Hospital to determine the effect of the workload of nurses working in surgical clinics on patient safety, it was determined that workload affected patient care and patient safety. It was concluded that increasing workload reduces the time devoted to the patient and increases the risk of errors as a result of fatigue and carelessness [12]. Sarıdiken and Çınar (2021) stated that excessive workload in the healthcare sector negatively affects the performance of employees, the quality of patient care, and patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted at Başkent University Ankara Hospital to determine the effect of the workload of nurses working in surgical clinics on patient safety, it was determined that workload affected patient care and patient safety. It was concluded that increasing workload reduces the time devoted to the patient and increases the risk of errors as a result of fatigue and carelessness [12]. Sarıdiken and Çınar (2021) stated that excessive workload in the healthcare sector negatively affects the performance of employees, the quality of patient care, and patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the presence of complex medical devices and equipment in surgical clinics, the risk of undesirable events such as injury or accident is higher than in other clinics. [6][7] For this reason, nurses working in surgical clinics have the responsibility to provide safe care for safe surgical processes, which reduces the risk of damage to patients before and after surgery. 8 The concept of patient safety is an important concept that depends on the characteristics of nurses, clinics and patients in the surgical field.…”
Section: Introductionmentioning
confidence: 99%
“…Aşırı iş yükü, uzun çalışma saatleri, yetersiz sayıda hemşire, gelişmiş teknolojiyle birlikte artan tıbbi cihazların varlığı, eksik malzeme, stresli çalışma ortamı gibi olumsuz çalışma koşulları hemşirelerin hasta güvenliği konusunda daha fazla risklerle karşılaşma olasılığını artırmaktadır (Rodrigues, Santos ve Sousa, 2017). Bu duruma çalışılan birim açısından bakıldığında ise hastanelerde cerrahi birimler olarak bilinen cerrahi klinikler, ameliyathaneler, acil birimler ve cerrahi yoğun bakım üniteleri kritik düşünmenin, çabuk karar vermenin ve uygulamanın acil olarak yaşama geçirilmesi gereken, birebir ekip çalışmasını gerektiren sirkülasyonun yüksek, stres faktörünün yoğun yaşandığı birimler olarak hasta güvenliği açısından büyük öneme sahiptir (Anderson, 2015;Erdağı ve Özer, 2015;Karahan, Çelik ve Sugeçti, 2021). Meydana gelebilecek olumsuz olayların azaltılmasında ya da ortadan kaldırılmasında sağlık kurumlarında etkin bir hasta güvenliği kültürünün geliştirilmesi büyük önem taşımaktadır (Barsbay, Parıltı ve Çakmak Barsbay, 2018).…”
Section: Introductionunclassified